RANCANGAN SISTEM PENDETEKSI GAS BLERANG BERBASIS ARDUINO UNO - Amin, Muhammad; Sarif, Muhammad Irfan; Rahmatullah, Ahmad Dzaki (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2023)
Doulu Village is a village located in Brastagi District, Karo Regency, North Sumatra Province which is quite well known because it has quite interesting tourist objects to visit. A village that presents the location of tourist attractions in the village displays a natural charm that is quite amazing for local and foreign tourists. Doulu Village has many locations for blerang water baths and mountain hot springs, this is what makes the tourist attraction quite good and healthy for tourists. The problem obtained from this tourist attraction is that there is no information about the gas levels produced by the blerang water which is quite concentrated which can suffocate the breath of visitors or tourists who will visit the blerang hot springs in Doulu Village, Berastagi District, Karo Regency. technology is needed that can provide information on a system for detecting sulfur gas levels produced from hot water vapor at a hot spring tourist attraction in Doulun Village, Berastagi District, Karo Regency. So that tourists who want to travel to the hot springs tourist attraction in Doulu Village can still breathe fresh air produced from the natural mountains which are still quite beautiful. To overcome this problem, the authors will conduct a study to detect the levels of sulfur gas produced from hot water vapor from natural attractions in Doulu Village. The intelligent system developed in this study will use an Arduino microcontroller and sensors that can detect the levels of sulfur gas produced from the hot water vapo.